If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2*z)/5-x^2 = 40 // - 40
(2*z)/5-x^2-40 = 0
-1*x^2 = -(2/5*z-40) // : -1
x^2 = 2/5*z-40
x^2 = 2/5*z-40 // ^ 1/2
abs(x) = (2/5*z-40)^(1/2)
x = (2/5*z-40)^(1/2) or x = -(2/5*z-40)^(1/2)
x in { (2/5*z-40)^(1/2), -(2/5*z-40)^(1/2) }
| y=6x^3-48 | | x^2/6-x/2-3=0 | | y=3/7(x-7)+2 | | 7x-12x*5=-45+15 | | x-5.5=5.6 | | -0.6x-10=0.3 | | 20-4[c-3-6(2c+3)]=5(3c-2)-[2(7c-8)-4c+7] | | 0.9x-4.2=3.0 | | 1=v+5 | | 0.07y+0.08(200-y)=0.24y | | 12=4-(x/2) | | 16=-3b+4b | | 10.6z-9.6z+3.8=2.9 | | 2(9+7)-7=9 | | 5(x*6)+3=-7 | | h=vt-5t | | 6(x-6)-60=9x-3(x-4) | | 7.2=2.5y-1.5y+6.9 | | -7(x+2)+3x+7=5x+12 | | -15e+7p-(-11e)+(-13p)= | | x=7/2 | | 12x+3x=2-6+4x | | 2(7x-9)=14x-18 | | 3/8+b/8=5/12 | | 8(n-1)=-24 | | 2.5z-1.5z+8.7=7.2 | | -3x+6-5(x-1)=-5x(2x-4)+5 | | 2/6=a/2 | | 0.12(y-9)+0.18y=0.02y-0.01 | | x/36=2/9 | | 4x-3=6x+5 | | 32/4=x/2 |